The Strategic Influence of Learning and Spatial Intelligence on the Mathematic Study of Discrete Students in the Informatical Technical Studies Program - Nuke Lu'Lu Ul Chusna S; Zulfiati Syahrial; Nurdin Ibrahim (EDUCATIO: Journal of Education)
Students' learning outcomes do not correspond to expected skill levels. This is because, in the learning process, teachers still dominate, using lectures or traditional approaches to influence student learning results. This study aims to investigate the influence of learning strategies and spatial intelligence on discreet mathematical learning outcomes.  The Experimental Method is used in this investigation, with the Treatment by Level 2 x 2 design treatment plan. Results of research using the ANAVA Two-Way Test, where there is a treatment variable, the Instructional Strategy (A), which consists of two class groups, namely the class group that is treated with the Inquiry Instructional Strategies (A1) and the control class group which is the Conventional Instructional Strategies (A2). There is a moderator variable, namely Spatial Intelligence (B), which consists of a group of High Space Intelligence (B1) and a low spatial intelligence group (B2). The findings of this study revealed that discrete mathematical learning outcomes of students studying with inquiry instructional strategies were higher than discrete mathematical learning outcomes of students studying with conventional instructional strategies, that there was no influence of interaction between instructional strategy with spatial intelligence on discrete maths learning output, and that there were significant differences between discrete mathematic learning outputs of students with inquiry instructional strategies and students with conventional instructional strategies.